2019
DOI: 10.1038/s41436-018-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Germline cancer susceptibility gene variants, somatic second hits, and survival outcomes in patients with resected pancreatic cancer

Abstract: Nearly 10% of PDAC patients harbor germline variants, although the majority lack somatic second hits, the therapeutic significance of which warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 38 publications
7
151
2
1
Order By: Relevance
“…5,6,8,9,11,25,[47][48][49][50][51][52][53][54][55][56][57]. Importantly, in one study that showed that nearly 10% of PDAC patients carried a germline ATM mutation, in 44% of these patients a somatic second hit was identified (58). Although this loss-of-heterozygosity (LOH) seems to occur frequently in tumors arising from patients with germline ATM mutations (e.g., as seen in breast and pancreatic cancers; refs.…”
Section: Inactivating Atm Variants In Pancreatic Cancermentioning
confidence: 99%
“…5,6,8,9,11,25,[47][48][49][50][51][52][53][54][55][56][57]. Importantly, in one study that showed that nearly 10% of PDAC patients carried a germline ATM mutation, in 44% of these patients a somatic second hit was identified (58). Although this loss-of-heterozygosity (LOH) seems to occur frequently in tumors arising from patients with germline ATM mutations (e.g., as seen in breast and pancreatic cancers; refs.…”
Section: Inactivating Atm Variants In Pancreatic Cancermentioning
confidence: 99%
“…In these familial PDAC cases, germline mutations in, among others, BRCA1 , BRCA2 , ATM , BRIP1 , CHEK2 , NBN , PALB2 , RAD50 , RAD51C and MLH1 are frequently detected [19,20,21,22,23]. Intriguingly, these genes encode proteins involved in different DNA repair pathways, including homologous recombination-mediated DNA double-strand break (DSB) repair and mismatch repair.…”
Section: Inherited Pancreatic Cancer Riskmentioning
confidence: 99%
“…This is particularly important for ATM aberrations in CLL, as these are subclonal to a large extend [93]. Nevertheless, given that a relatively large proportion of PDAC patients carries germline aberrations in known HR genes, including BRCA1 , BRCA2 , PALB2 , and ATM [19,20,21,22,23], PDAC may represent an entity in which PARP and/or DNA-PKcs inhibitors may be effective as single agents or as part of combination regimens. …”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 99%
See 2 more Smart Citations